2020
DOI: 10.14256/jce.1982.2017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of friction damper on seismic response of structure considering soil-structure interaction

Abstract: The effect of soil structure interaction (SSI) on a single degree of freedom system with and without friction damper is analysed in the paper. The structure with different mass, stiffness and soil conditions was prepared and analysed for ten different earthquake records. Using the non-linear time history analysis, the structural response of a single degree of freedom structure with varying slip load of friction damper was studied. It was observed that the performance of friction dampers is influenced by soil p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Therefore, in this study, the damping ratio is estimated using the Half-Power Bandwidth as shown in Eq. ( 5) [22].…”
Section: Foundation Dampingmentioning
confidence: 99%
“…Therefore, in this study, the damping ratio is estimated using the Half-Power Bandwidth as shown in Eq. ( 5) [22].…”
Section: Foundation Dampingmentioning
confidence: 99%
“…The different structural configurations, impact models, analyses, and assumptions considered in these studies have indicated that structural pounding amplifies structural responses. Another exaggerating factor is the soil effect, which involves the sliding, rotation, and settlement of foundations during earthquakes [13][14][15][16][17][18][19][20][21]. The assumption of a fixed base that neglects the soil effect is sufficient for structures with low structural rigidity, in which the displacement of the superstructure is more important than that of the foundation.…”
Section: Introductionmentioning
confidence: 99%
“…Structural scientists focused on strengthening structures, as well as the optimal design of buildings under earthquakes loads. The design of new buildings, including seismic restraint systems, is one of the new structural topics in recent decades (Nizic & Mestrovic, 2011;Majd et al, 2019;Sanghai & Pawade, 2020). These systems only act against various seismic vibrations without withstanding any static loads.…”
Section: Introductionmentioning
confidence: 99%